If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -64 = -6x + 62 Reorder the terms: -64 + X = -6x + 62 Reorder the terms: -64 + X = 62 + -6x Solving -64 + X = 62 + -6x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + X = 62 + 64 + -6x Combine like terms: -64 + 64 = 0 0 + X = 62 + 64 + -6x X = 62 + 64 + -6x Combine like terms: 62 + 64 = 126 X = 126 + -6x Simplifying X = 126 + -6x
| 6x+4x-2=16 | | 44=-4(1+6b)-6(-5b-1) | | 59+11p=-29 | | 3(5e-3)=e+4 | | 6a+a=84 | | 30(6)+5y=90 | | X-43=-4x+27 | | 8x+10y=12-8x | | .45x=9 | | 140+2x-y=180 | | 3(5x-5)=x+10 | | 0=4.9t^2-14.7t | | 20x-x^2=100 | | 3+5h=7+2h | | 8(4r-9)=r+27 | | x+(x+4)+(x+8)=21 | | -7-(n-1)=-6(1-2n) | | y=x^2+7x+9 | | 4x-11=x-9 | | 3a+3=54 | | 8(-1+5x)=112 | | 30=9x+y | | x+10-7=4(x+6)-2(3x+3) | | 103-x=2x+6x-7 | | 8w-13w=25 | | 7b^2+-14b+1=0 | | 4x+11=5x-5 | | 4x+8=2x+31+51 | | 12+40=62 | | 3k-1=7x+2 | | 6+2(x+7)=10-3(x-3) | | 40x^2-x+4000=0 |